Estimating Household Preferences for Coastal Flood Risk Mitigation Policies Under Ambiguity. Issue 12 (14th December 2022) - Ha, Si; Fujimi, Toshio; Jiang, Xinyu; Mori, Nobuhito; Begum, Rawshan A.; Watanabe, Masahide; Tatano, Hirokazu; Nakakita, Eiichi
Abstract: Risk mitigation policies (like dike rising) are essential to address increasing coastal flood risks due to global warming. Furthermore, the optimal level of risk mitigation policy should be determined by public preferences for risk reduction. However, it is difficult to reveal public preferences for coastal flood risk reduction because projections of coastal flood risks inevitably involve uncertainty. This study aims to estimate household preference for coastal flood reduction under ambiguity and multiple projections of coastal flood risks. By coupling storm surge inundation simulations and stated preference experiments with decision models, we estimate the expected loss reduction, risk premium, and ambiguity premium for coastal flood risk mitigation policies. The study shows that ignoring the ambiguity premium causes significant undervaluation of coastal flood risk mitigation. Plain Language Summary: Climate change has contributed to more frequent and severe storm tide in coastal areas and enhanced flood risk. Thus, risk mitigation policies are essential to address increasing coastal flood risks from global warming. The policymakers must integrate multiple projections of coastal flood risk to make policy decisions. These decisions should reflect stakeholders' preferences on risk and ambiguity. Risk is uncertainty with a clear probability distribution, and ambiguity is uncertainty without a clear probability distribution. Currently, this key requirement has not yet been met. To fill this gap, this study investigates residents' preference to mitigate flood risk under ambiguity by coupling flood simulation and surveying residents on their willingness to pay for insurance to mitigate risk under average and worst‐case scenarios. The ambiguity premium is an additional payment for an individual to reduce flood risk with an unknown probability distribution in comparison to flood risk specified with a well‐known probability distribution. We found that ignoring ambiguity premium causes undervaluing coastal flood risk mitigation. Key Points: We couple flood simulation with a stated preference experiment to investigate residents' preference to mitigate flood risk under ambiguity Economic values of coastal flood risk mitigation measures are estimated by reduction of expected loss, risk premium and ambiguity premium Ignoring ambiguity premium might cause an undervaluation of coastal flood risk mitigation